"Whole Chinese angelica" microemulsion: its preparation and in vivo and in vitro evaluations. (October 2014) - Du, Hong; Feng, Qianjin; Yang, Xuezhi; Xu, Rongting; Li, Haiyan; Dong, Xiaoying; Zhu, Qingwen; Wang, Danwei; Lu, Xiaoyan; Niu, Xin
Abstract Context: The difference between the chemical polarities of the two categories of active chemical constituents in Chinese angelica volatile oil (CAVO) and Chinese angelica water extract (CAWE) greatly limit the development and clinical application of Chinese angelica preparation. Object: The aim of this study is to design and prepare a "whole Chinese angelica" microemulsion (WCAM) that contains both CAVO and CAWE and at the same time to evaluate it in vivo and in vitro. Materials and methods: CAVO and CAWE extracted from Chinese angelica were used as the oil and aqueous phases, respectively, to prepare the WCAM; its physicochemical property was observed, and its drug potency and oral bioavailability were evaluated. Results: The formula of the WCAM was optimized as Tween-80:ethanol:CAVO:CAWE = 3:3:1:40. The droplet size of the WCAM was 72.64 nm and the WCAM was proved to be physicochemically stable when it was kept at 0 °C, 4 °C, 25 °C and 40 °C for 3 months. The WCAM could markedly prolong blood clotting time, decrease whole blood viscosity and whole blood reduced viscosity at different shear rates, and improve hemorheological parameters. The results of the pharmacokinetic evaluation show that the AUC0–7 of the WCAM was 4510.66 and was about 4.41-fold compared to that of danggui concentrated pills (an existing Chinese angelica pharmaceutical preparation). Conclusion: It can be concluded, that the WCAM is a promising Chinese angelica preparation that has great prospects in the treatment of dysmenorrhea and irregular menstruation.